Penyuluhan Kesehatan Manfaat Pemberian ASI untuk Pencegahan terjadinya Stunting pada Anak Kepada Ibu-Ibu Pengajian Aisyiyah Cabang Klangenan Kabupaten Cirebon - Marwati Marwati; Sofiyati Sofiyati (Jurnal Informasi Pengabdian Masyarakat, 2026)
Stunting remains a major chronic nutritional problem in Indonesia, as it affects physical growth, cognitive development, and the quality of human resources in the future. One effective strategy to prevent stunting is the provision of exclusive breastfeeding during the first six months of life as part of interventions in the first 1,000 days of life. This community service activity aimed to improve the knowledge of mothers in the Aisyiyah Islamic study group, Klangenan Branch, Cirebon Regency, regarding the importance of breastfeeding, adequate nutrition, and the role of the first 1,000 days of life in preventing stunting in children. The method used was health education through lectures, discussions, and question-and-answer sessions. The results showed an increase in participants’ understanding of the benefits of exclusive breastfeeding, appropriate infant feeding practices, and the importance of fulfilling nutritional needs from pregnancy until the child reaches two years of age. With improved maternal knowledge, positive behavioral changes in breastfeeding practices and child nutrition are expected. This activity contributes to promotive and preventive efforts to reduce stunting rates, particularly in Cirebon Regency.